Analisis perpindahan tenaga kerja informal Kabupaten Pasuruan - Wijaya, Kusuma; Syairozi, Muhamad Imam (Program Studi Ekonomi Pembangunan Fakultas Ekonomi dan Bisnis Universitas Jambi, 2020)
The uneven economic growth causes regions to experience economic and social inequalities, which in the end they choose to look for a place that is expected to be able to meet their physical and spiritual needs. This study aims to determine the dominant factors that influence the decisions of informal workers to migrate to Pare District, Kediri Regency. The method of collecting direct data is by conducting interviews with respondents. The data obtained were then analyzed by the SPSS program using logistic regression analysis. The independent variables studied include: age (X1), an education level (X2), land ownership (X3), marital status (X4), employment status (X5), income (X6) and the dependent variable in this study is the decision to migrate. (Y). Based on the data collected from 102 respondents, it is known that the variables age (X1), land ownership (X3), and income (X6) have a significant effect on the reasons a person decides to migrate to Sukorejo District, Pasuruan Regency. While the education variable (X2), marital status (X4), and employment status (X5) were not significant. The income variable (X6) is the variable that most dominantly influences the decision of an informal worker to migrate to Sukorejo District, Pasuruan Regency